Rainfall runoff model for mountainous area by using HEC-HMS case study - Cameron Highland - Sharmila, Sewajje (2016)
This study is focused on discharge estimation in a mountainous watershed in which three rivers at CAMERON HIGHLAND are chosen as the case study based on the rainfall distribution. The three rivers are Sg.Lemoi, Sg.Bertam and Sg.Telum. The rainfall-runoff model is simulated using Hydrological Modelling System (HEC-HMS) version 3.5. The rainfall data and stream flow data used in this study are from four rainfall stations (RF4218042, RF4414037, RF4414038, RF4514032) and two stream flow stations (SF4218416, SF4219415). The data used from the rainfall and stream flow stations are from the period of 1999 until 2014. The precision of data used during calibration and verification process depends on parameter used in HEC-HMS. Results of simulation can be generated in the form of time series table, summary table and hydrograph. Root Mean Square Error (RMSE) calculated to show the relationship of the simulated flow and the observed flow. If the RMSE value is lesser, it would indicate that the variables are positively linear related. During evaluation of model, the best value of RMSE value is 11.1